Tracing Sustainability in the Long Run - McLaughlin, Eoin,Ducoing, Cristián,Oxley, Les (National Bureau of Economic Research, 2023)
We introduce a new database of historical Genuine Savings (GS), an indicator of sustainable development promoted by the World Bank and widely used in contemporary economic research. GS derives from the theoretical work on wealth accounting, and addresses shortcomings in conventional metrics of economic development by incorporating broader measures of saving and investment, including human capital (education), and natural resource depletion. Its value as an indicator is determined by its ability to be used to predict future well-being. This article provides consistent historical estimates of GS since 1850 for 25 countries to enhance, complement, and contextualise the work of the World Bank and others
Hardcopy version available to institutional subscribers
Keywords: Arbeitspapier; Graue Literatur; Wirtschaftsindikator; Sparen; Nachhaltige Entwicklung; Wirtschaftswachstum; Welt; General; International; or Comparative; Sustainable Development; Exhaustible Resources and Economic Development; Environment and Development; Environment and Trade; Sustainability; Environmental Accounts and Accounting; Environmental Equity; Population Growth